A Computer-Aided Diagnosis System for the Detection and Classification of Breast Cancer. Issue 2 (April 2016) - Mohammed, Sahar H.A.; Yousuf, Soha E.K.
Abstract : Breast cancer is currently the foremost cause in women's mortality worldwide. In Sudan, the increasing incidence, detection at late stages, and the early onset of the disease make early detection and diagnosis of breast cancer an overbearing task. The objective of this study is to create an automated computer interfacing system for the localization, detection, and classification of breast mass. This study is implemented using MATLAB software. A Graphical User Interface is designed for the implemented algorithm. Results demonstrated that the proposed methodologies have high potential localizing, detecting, and classifying the breast tumor. The system was able to achieve an accuracy of 88% sensitivity, 72% specificity, an Az value of 0.84, and an overall classification accuracy of 80%. The created systems have therefore proved to effectively discriminate between malignant and benign tumors with an effective level of precision.